Rancang Bangun Penyimpanan Ikan Multi Fungsi (Unibox) - Abdi, Ferly Isnomo; Achmad, Fendi; Puspitasari, Dewi; Wijaya, Nieke Andina; Sulistyorini, Elisa (Jurnal Rekayasa Mesin, 2023)
The fishing industry holds significant importance in Indonesia, relying heavily on fishermen to ensure the quality of fish remains intact from the sea to the hands of distributors. However, traditional fishermen often encounter obstacles due to limited cooling facilities, leading to compromised fish quality and potential spoilage prior to sale. Moreover, conventional fishing methods consume considerable time and fuel resources. To enhance the efficiency and productivity of fishermen, there is a need for technological advancements such as a versatile fish storage solution known as Unibox. This innovation incorporates self-sustaining power generation, fish tracking technology, eco-friendly fish preservation methods, and efficient boat illumination systems. Unibox is anticipated to enhance fishermen's livelihoods, contribute to national food security initiatives, and provide a platform for students to gain firsthand industry experience.